The benefit of wrapping trees in biodegradable material netting to protect against bark stripping by bears extends to surrounding stands - Kobashikawa, Shoko (2019)
Bark stripping by Asian black bears (Ursus thibetanus) has a serious impact on conifer plantations in Japan. Prevention strategies tend to be implemented on a tree-by-tree basis by wrapping standing trees in biodegradable tape or netting. It remains unclear, however, whether installing these materials has a beneficial effect on untreated trees in surrounding stands. The aim of this study was to clarify the effects of installing these materials on bark stripping by bears in neighboring areas. The study was conducted in eastern Gunma Prefecture, central Japan. We selected 113 stands of Cryptomeria japonica and Chamaecyparis obtusa treated with these materials and 162 untreated stands (7963 trees). In untreated stands, we established square plots and calculated the rates of damage by bears. Generalized linear mixed models were used to analyze the effects of various factors on bark stripping, and segmented regression analysis was used to determine whether the rate of bark stripping in untreated stands had increased after material installation in treated stands. The rates of damage to Japanese cedar and Japanese cypress by bears in treated stands 1 or 2 years after material installation were 0% and 0%, respectively. In contrast, rates of damage to Japanese cedar and Japanese cypress in untreated stands surrounding the treated stands were 2.6% ± 1.8% and 2.7% ± 1.2%, respectively, at 1 year and 2.7 ± 1.5% and 2.8 ± 1.2%, respectively, at 2 years after material installation. We found that bark stripping by bears tended to occur in untreated stands far from treated stands at 1 or 2 years after installation. The segmented regression models showed that the rate of occurrence of bark-stripping damage at 1 and 2 years after treatment was markedly lower in untreated stands close to treated stands than in those beyond the breakpoints, and it increased only weakly in farther stands. Our findings indicate that installing tape or netting in selected stands can curb the occurrence of bark-stripping damage in surrounding stands within a certain distance. That is, material installation in individual stands did not lead to displaced bark-stripping activity in surrounding areas.